Self-help in health care - Robinson, David (1980)
This paper was given at a London Medical Group symposium held at Middlesex Hospital Medical School in May 1979, on `Self-help groups - England's barefoot doctors'. Dr Robinson gives a brief history of some of the reasons why self-help groups have evolved and how they work. He also looks at how the `professionals' can and do relate to them.